Event shape analysis of deep inelastic scattering events with a large rapidity gap at HERA - Breitweg, J; Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Yoshida, R; Zhang, H; Mattingly, M; et al. (1998)
A global event shape analysis of the multihadronic final states observed in neutral current deep inelastic scattering events with a large rapidity gap with respect to the proton direction is presented. The analysis is performed in the range 5 ≤ Q2 ≤ 185 GeV2 and 160 ≤ W ≤ 250 GeV, where Q2 is the virtuality of the photon and W is the virtual-photon proton centre of mass energy. Particular emphasis is placed on the dependence of the shape variables, measured in the γ * -pomeron rest frame, on the mass of the hadronic final state, MX. With increasing MX the multihadronic final state becomes more collimated and planar. The experimental results are compared with several models which attempt to describe diffractive events. The broadening effects exhibited by the data require in these models a significant gluon component of the pomeron. © 1998 Elsevier Science B.V.